Case Report: Anomalous Experience in a Dissociative Identity and Borderline Personality Disorder - Martins, Hugo André de Lima; Ribas, Valdenilson Ribeiro; dos Santos Ribas, Ketlin Helenise; da Fonseca Lins, Luciano; Mainieri, Alessandra Ghinato (Frontiers in Psychiatry, 2022)
Introduction: Dissociative identity disorder, formerly called multiple personality disorder, is a rupture of identity characterized by the presence of two or more distinct personality states, described in some cultures as an experience of possession. Objective: The case of a 30-year-old woman with dissociative identity disorder and borderline personality disorder associated to a previous history of anomalous experience was reported. Case report: A 30-year-old woman who fulfilled the DSM-5 criteria for dissociative identity disorder and borderline personality disorder reported the presence of unusual sensory experience (clairvoyance, lucid dreams, premonitory dreams, clairaudience) since she was five years old. The patient told that for 12 months, presented episodes in which a “second self” took charge of her actions, when then she spoke with a male voice, becoming aggressive, requiring several people to contain her desire of destruction. After three months on religious follow-up accepting as normal and naturalized her unusual experiences and trance possessions, she had significant improvement. Conclusion: It is necessary to consider anomalous phenomena presented by patients with dissociative identity and borderline personality disorder and the importance of cultural and religious context for the disorder’s evolution with improvement of the outcome, which has not been explored in the treatment’s guide.